STUDENTS’ PREFERENCES IN ONLINE DISTANCE LEARNING DURING COVID-19 - Nor Azira Mohd Radzi; Nor Alifah Rosaidi; Noorazalia Izha Haron; Azhar Abdul Rahman (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The educational community is in shambles as a result of the COVID-19 pandemic. Pre-diploma students have particular challenges since they are unfamiliar with higher education, lack the tools necessary for efficient online distance learning, and are not academically driven. Pre-diploma UiTM students are primarily from low-income families. This aggravates problems with their online learning environment. University students must be independent learners due to the high demand for online education when the epidemic occurs. This study aims to look into 35 pre-diploma students’ views on their autonomy in online English classes. The information was gathered near the end of the semester. Students asserted that their level of control over their online learning was minimal at the start of the semester, as was to be expected. They spent weeks trying to take control of their academic lives. The students discovered, however, that by the seventh week, they had more control over their online learning, indicating that they were beginning to understand what was happening in their virtual English classrooms. Once they understood that this is the only way to learn during the pandemic, they felt more at ease with their liberty in learning. This study also discovered that these brand-new undergrads positively embraced and adopted online learning as a novel method of training.